DATA LOCALIZATION REQUIREMENT - Zarina Behzod kizi , Kamarova (Educational Research in Universal Sciences, 2024)
This article explores the importance of personal data protection regulation in Uzbekistan and its impact on international business, trade, and e-commerce in the country. It highlights the significant changes brought about by the Personal Data Protection Act, focusing on its influence on data transfer, cross-border business operations, consumer trust, and competitiveness in the global market. The article concludes with recommendations for businesses operating or seeking to expand into Uzbekistan to ensure compliance and build a strong foundation for success in the evolving digital era.